A comparative study of behaviors of ventilated supercavities between experimental models with different mounting configurations. (20th July 2016) - Lee, Seung-Jae; Kawakami, Ellison; Karn, Ashish; Arndt, Roger E A
Abstract: Small-scale water tunnel experiments of the phenomenon of supercavitation can be carried out broadly using two different kinds of experimental models–in the first model (forward facing model, or FFM), the incoming flow first interacts with the cavitator at front, which is connected to the strut through a ventilation pipe. The second model could have the strut and the ventilation pipe preceding the cavitator (backward facing model, or BFM). This is the continuation of a water tunnel study of the effects of unsteady flows on axisymmetric supercavities. In this study, the unwanted effect of test model configuration on supercavity shape in periodic flows was explored through a comparison of FFM and BFM models. In our experiments, it was found that periodic gust flows have only a minimal effect on the maximum diameter and the cavity length can be shortened above a certain vertical velocity of periodic flows. These findings appear to be robust regardless of the model configuration.